Case report: Nonsimultaneous bilateral triceps tendon rupture and surgical repair in a healthy dog - Bennett, Maureen P.; Silver, Gena; Tromblee, Tonya; Kohler, Rickard; Frem, Daniel; Glass, Eric N.; Kent, Marc (Frontiers in Veterinary Science, 2024)
A 7-year-old female spayed Australian shepherd dog was presented for an acute onset of inability to stand. On physical examination, the dog was unable to support weight on the thoracic limbs. On neurological examination, the thoracic limbs had absent hopping and paw placement and reduced withdrawal reflexes bilaterally. The remainder of the neurological examination was normal. The anatomic lesion localized to the C6-T2 spinal nerve roots, spinal nerves, or the named nerves of the thoracic limb, bilaterally. A lesion affecting the ventral gray column of the C6 through T2 spinal cord segments was considered less likely. In an effort to exclude an orthopedic disorder from consideration, radiographs of the shoulders, elbows, and manus were normal. Magnetic resonance imaging of the cervical and cranial thoracic vertebral column was normal. Analyses of synovial fluid from the carpi, elbows, and shoulders were normal.Ultrasonography of the triceps muscle and tendon of insertion revealed bilateral, acutesubacute tears of the tendon at insertion of the triceps muscles, bilaterally. Magnetic resonance imaging of both elbows revealed complete avulsion of the triceps tendons bilaterally. Surgical repair of both tendons was performed using the Arthrex FiberLoop system combined with autologous conditioned plasma soaked in a collagen sponge.Postoperatively, external coaptation was provided using Spica splints for six weeks followed by the use of soft padded orthotic braces for an additional six weeks. Concurrently, a front support wheelchair was used for 10 weeks postoperative. By 10 weeks postoperative, the dog was able to ambulate without support. To the authors' knowledge, this is the first report of bilateral triceps tendon avulsion in a dog. Tendon avulsion occurred without a known history of trauma or predisposing metabolic abnormalities. Magnetic resonance imaging provided excellent anatomical detail that aided in surgical repair.